Analisis Promosi Instagram Melalui Pendekatan AISAS pada Atlantis Water Adventure Ancol - Syifa Ul Aulia; Andi Muhammad Sadat; Dewi Agustin Pratama Sari (Universitas 45 Surabaya, 2025)
This study aims to examine the social media marketing activities of Instagram for Atlantis Water Adventure Ancol. Data collection was conducted using a survey with a questionnaire distributed online. The population of this study consists of people in DKI Jakarta who meet the following criteria: aged 18 years and above, have an Instagram account, and have seen promotional content from Atlantis Water Adventure Ancol on Instagram. This study involved 200 respondents, and the data were analyzed using SPSS Version 29 for validity and reliability testing, as well as data testing using average scores. The results show that the AISAS method (Attention, Interest, Search, Action, and Share) is highly effective in social media marketing for Atlantis Water Adventure Ancol on Instagram.